Variables associated with knee valgus in male soccer players during a single leg vertical landing task - Leporace, G.; Vianna, M.; Metsavaht, L.; Tannure, M.; Maior, A. S. (British Journal of Sports Medicine, 2021)
Background Knee valgus during landing and cutting situations has been described as the main biomechanical risk factor for anterior cruciate ligament (ACL) injuries. Evidence support the influence of hip strength and biomechanics on knee valgus in female athletes. To develop specific preventive measures for males, it is important to understand biomechanical and musculoskeletal variables associated with this mechanism during activities that mimic ACL injuries.